2000
DOI: 10.1086/308740
|View full text |Cite
|
Sign up to set email alerts
|

The RASSCALS: An X‐Ray and Optical Study of 260 Galaxy Groups

Abstract: We describe the ROSAT All-Sky Survey-Center for Astrophysics Loose Systems (RASSCALS), the largest X-ray and optical survey of low mass galaxy groups to date. We draw 260 groups from the combined Center for Astrophysics and Southern Sky Redshift Surveys, covering one quarter of the sky to a limiting Zwicky magnitude of m z = 15.5. We detect 61 groups (23%) as extended X-ray sources.The statistical completeness of the sample allows us to make the first measurement of the X-ray selection function of groups, alon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
165
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(168 citation statements)
references
References 50 publications
(68 reference statements)
3
165
0
Order By: Relevance
“…But, what is observed from the upper panel of Figure 8 is that groups with σ gr ≤ 200 km s −1 have higher L X in comparison with their σ gr . This same phenomenon was observed before by dell 'Antonio et al (1994); Mahdavi et al (2000); Mahdavi & Geller (2001); Helsdon et al (2005); Rines & Diaferio (2010).…”
Section: X-bootessupporting
confidence: 88%
See 1 more Smart Citation
“…But, what is observed from the upper panel of Figure 8 is that groups with σ gr ≤ 200 km s −1 have higher L X in comparison with their σ gr . This same phenomenon was observed before by dell 'Antonio et al (1994); Mahdavi et al (2000); Mahdavi & Geller (2001); Helsdon et al (2005); Rines & Diaferio (2010).…”
Section: X-bootessupporting
confidence: 88%
“…In studies of poor systems, Mahdavi et al (2000) and Xue & Wu (2000) found L X ∝ σ 1.38±0.4 and L X ∝ σ 2.35±0.21 , flatter than the theoretical expectation for a self-similar model, L X ∝ σ 4 . Helsdon & Ponman (2000) (L X ∝ σ 2.4±0.4 ) and Osmond & Ponman (2004) (L X ∝ σ 2.31±0.62 ) also found significantly flatter relations in groups.…”
Section: Introductionmentioning
confidence: 74%
“…Dell'Antonio et al (1994) and Ponman et al (1996) showed that rich groups follow the L X ∼ σ 4 v relation, but groups with smaller RVD (<300 km s −1 ) have a more shallow slope. Mahdavi et al (2000) showed that the correlation between L X and σ v may be best represented by a broken power law with a ∼ 1.4 for galaxy groups and a ∼ 4 for galaxy clusters. Figure 20 shows that ShCGs represent the low-mass extension of clusters and have sufficiently large dispersion 5 .…”
Section: The Physical State Of Shcgsmentioning
confidence: 99%
“…It was identified as an extended X-ray source in the ROSAT All-Sky Survey with an X-ray luminosity of 3.33 × 10 43 h −2 50 erg s −1 in the 0.1-2.4 keV band within an aperture of 1.0 h −1 50 Mpc (NRGs241; Mahdavi et al 2000). Global fitting of the ASCA SIS and GIS data by Davis et al (1999) yielded a mean gas temperature of 1.02 ± 0.05 keV, an average abundance of 0.26 that a two-temperature spectral model provides a better fit to the ASCA spectra of RGH 80 and has a metallicity that is substantially higher than that obtained by the single temperature spectral model, Z = 0.67…”
Section: Introductionmentioning
confidence: 99%